Iron dienylphosphate tricarbonyl complexes as water-soluble enzyme-triggered CO-releasing molecules (ET-CORMs) - Romanski, Steffen; Stamellou, Eleni; Yard, Benito A. (Organometallics, 2012)
A series of racemic phosphoryloxy-substituted (η4-cyclohexadiene)Fe(CO)3 complexes was synthesized by exploiting the O-phosphorylation of (dienol)Fe(CO)3 intermediates generated in situ from the corresponding triisopropylsiloxy-protected complexes. The phosphorylated products were fully characterized by spectroscopic methods, including single-crystal X-ray diffraction in four cases. Monodeprotection of two dimethyl phosphate derivatives with trimethylamine led to the tetramethylammonium salts of the (cyclohexadienyl methyl phosphate)Fe(CO)3 complexes. These compounds are the first water-soluble enzyme-trigged CO-releasing molecules (ET-CORMs). The phosphatase-induced CO release was monitored by means of GC. The biological activity was assessed in different cellular assays. The compounds were shown to be only slightly toxic, and a moderate anti-inflammatory potential was determined in an assay based on the inhibition of inducible NO synthase (iNOS)-induced NO production.